Management of renewable-based multi-energy microgrids in the presence of electric vehicles - Shafie-khah, Miadreza; Vahid-Ghavidel, Morteza; Di Somma, Marialaura; Graditi, Giorgio; Siano, Pierluigi; Catalão, João P. S. (IET, 2020)
This study proposes a stochastic optimisation programming for scheduling a microgrid (MG) considering multiple energy devices and the uncertain nature of renewable energy resources and parking lot‐based electric vehicles (EVs). Both thermal and electrical features of the multi‐energy system are modelled by considering combined heat and power generation, thermal energy storage, and auxiliary boilers. Also, price‐based and incentive‐based demand response (DR) programs are modelled in the proposed multi‐energy MG to manage a commercial complex including hospital, supermarket, strip mall, hotel and offices. Moreover, a linearised AC power flow is utilised to model the distribution system, including EVs. The feasibility of the proposed model is studied on a system based on real data of a commercial complex, and the integration of DR and EVs with multiple energy devices in an MG is investigated. The numerical studies show the high impact of EVs on the operation of the multi‐energy MGs.
Keywords: boilers; distributed power generation; power system management; optimisation; electric vehicles; renewable energy sources; fi=Sähkötekniikka|en=Electrical Engineering|